2018
DOI: 10.1590/1983-40632018v4852302
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of nutrients by soursop seedlings in response to mycorrhizal inoculation and addition of organic compost1

Abstract: The use of organic composts and the inoculation of arbuscular mycorrhizal fungi (AMF) are management alternatives in organic production systems. This study aimed to evaluate the effect of AMF inoculation (Acaulospora scrobiculata, Acaulospora colombiana and without inoculation) and organic compost of cacao bark (0 g dm-3, 5 g dm-3, 10 g dm-3, 20 g dm-3 and 30 g dm-3) on the mycorrhizal efficiency and nutrient uptake, in 'Morada' soursop seedlings. The experimental design was completely randomized, in a 3 x 5 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
0
0
1
Order By: Relevance
“…Fertilizer and AMF had an interactive effect on plant growth, and applications of AMF and fertilizer mainly promoted plant growth by enhancing their nutritional status. The study showed that AMF and fertilizer promoted the increase in nitrogen and phosphorus content in plants, thereby promoting the growth and nutrition of seedlings [32], which was consistent with the results of this study. AMF can also increase the chlorophyll content of ryegrass to a certain extent and promote photosynthesis, phosphorus absorption and ryegrass growth [33].…”
Section: Effects Of Fertilizer and Arbuscular Mycorrhizal Fungi On Th...supporting
confidence: 91%
“…Fertilizer and AMF had an interactive effect on plant growth, and applications of AMF and fertilizer mainly promoted plant growth by enhancing their nutritional status. The study showed that AMF and fertilizer promoted the increase in nitrogen and phosphorus content in plants, thereby promoting the growth and nutrition of seedlings [32], which was consistent with the results of this study. AMF can also increase the chlorophyll content of ryegrass to a certain extent and promote photosynthesis, phosphorus absorption and ryegrass growth [33].…”
Section: Effects Of Fertilizer and Arbuscular Mycorrhizal Fungi On Th...supporting
confidence: 91%
“…At the end of the experiment, the concentrations of macronutrients and micronutrients in the shoots and roots of the A. angustifolia seedlings were generally higher in seedlings inoculated with AMF than in the control seedlings. Similarly, Moreira-Souza and Cardoso (2002) and Zandavalli et al (2004) reported that the nutrient concentrations in leaves were similar to those in one-year-old A. angustifolia seedlings, as were the concentrations of these nutrients in soursop seedlings (Gomes Júnior et al, 2018), jatropha (Saboya et al, 2012), and coffee (França et al, 2016).…”
Section: Discussionmentioning
confidence: 74%
“…Nessa perspectiva, o uso da secagem artificial para o cacau pode diminuir o tempo de secagem, intensidade de mão-de-obra, tamanho de área necessária para secagem e condições que possa depreciar o produto (BORÉM; REINATO; ANDRADE, 2015).Ainda, as amêndoas secas em menor tempo e temperatura (30 °C/ 6 horas) propiciaram a proliferação de fungos. Condição abordada nos estudosde Souza et al (2017),Garuzzo e Pereira (2018) e Gomes Júnior et al (2018, visto a importância de obter o teor de água adequado e prever possíveis perdas do produto.O consumo de energia na secagem está ligado a eficiência do equipamento de secagem (SILVA; LOPES;MELO, 2015), logo auxilia a comprovar a efetividade de protótipos secadores. O autor reitera a utilidade ao comparar equipamentos de diferentes fabricantes, quanto menor o consumo específico de energia mais econômico o dispositivo.…”
unclassified